UNDERSTANDING THE ROLE OF ATTENTION AND CONSCIOUSNESS IN COGNITIVE PSYCHOLOGY (Journal of Universal Science Research, 2024)
This article explores the essential concepts of attention and consciousness within the field of cognitive psychology. Attention is the process of selectively concentrating on specific stimuli, while consciousness encompasses our awareness of ourselves and our environment. This article delves into the relationship between attention and consciousness, their underlying mechanisms, and their significance in shaping human cognition and behavior.